Mapping the Intellectual Landscape of Character Education Research: A Systematic Literature Review of Trends, Themes, and Collaboration Networks - Irawan, Hendri; Sundawa, Dadang; Mustofa, Imam; Wijayanti, Tutik; Istianah, Anif (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to maps the intellectual landscape of character education research through a bibliometric-based Systematic Literature Review (SLR), focusing on the relationship between character education and civic education in the school context. Data were obtained from the Scopus database, where 522 documents were identified, limited to English-language journal articles published between 2016 and 2026. Bibliometric analysis was conducted using VOSviewer to identify publication trends, author contributions, affiliations, countries, and keyword co-occurrence patterns. The findings indicate a significant increase in publications on character education, with character education and civic education emerging as strongly interconnected central themes. The thematic mapping reveals several major clusters, including virtue ethics and moral values approaches, democratic civic education, curriculum and learners, methodological approaches based on human experiences, as well as pedagogical innovations such as project-based learning, empathy, and digital literacy. These findings indicate a shift in character education research from a normative approach toward a more integrative, contextual, and practice-oriented perspective. This study contributes theoretically by clarifying the intellectual landscape of character education research and this study supports policies promoting integrated character–civic curricula, whole-school approaches, innovative pedagogy, teacher professional development, and holistic assessment aligned with 21st-century educational challenges.